“Deshidratación osmótica de rodajas de carambola (avrrhoa carambola L.) en tres estados de madurez.” - Pérez Angulo, Llelith (2007)
The star fruit is a native product of the tropical zones of the Asian countries, adapted perfectly at San Martin. In order to improve the quality of fruit dehydrated in conventional driers, osmotic dehydration of star fruit slice in sucrose solution was studied. The objectives of the present work were to evaluate the influence of sucrose concentration in the solution and the maturity on the kinetic of moisture content and water activity reduction and sucrose gain and to determine the water and sucrose diffusion coefficient in each experiment and determine the sensory preference of the fruit osmotic dehydrated. The experimental design used was a central composition 22 , 2 central and 4 axial points. The star fruit slice of three maturity states was immersed in sucrose aqueous solutions (28, 40, 50 60 and 65%, p/p) for different times until 33 hours. The sucrose content was determined by DNS method and the moisture content by the stove method. The water activity was determined with the Aqualab 3TE. The effective sucrose diffusion coefficients were determined according the Fick's law. The kinetic showed that for 1 O hours and long time of osmotic dehydration, the solution concentration influenced significantly and not the maturity state on the moisture content. In other hand, both maturity state and solution concentration influenced significantly on suerosa content. The suerosa diffusion coefficients values fluctuated between 0,96 x10-9 m/s2 to 0,79 x10-9 m/s2 ; both maturity state and solution concentration influenced significantly on diffusion coefficients. The samples were then submitted to acceptability tests for texture, flavor and general appearance, performed by a panel of 20 judges, by using a hedonic scale of nine points, the results were obtained by means of the Software ,STATISTICA 5.0 forWindows.